Some aspects of state administration for innovation - Hai, Nguyen Hoang; Hai, Ha Cong; Trang, Nguyen Ha Quynh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2020)
For long years, the governments of many countries in the world follow different administration schemes in science and technology (S&T) sector. These efforts lead to radical development of S&T and then make effective contributions to industrialization and modernization of the countries. With the same vision, Vietnam follows his own scheme for State administration of S&T activities and achieves certain success. During recent years, the State administration approach with focus for innovation has created new trends in designing phase of policies and mechanisms and, more importantly, led to changes and new driving forces for socio-economic development in many countries. This paper is to provide initial studies for this topic on basis of theoretical consideration and practical implementation in Vietnam. Code: 19120901